2020
DOI: 10.1080/00268976.2020.1776903
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy surfaces of charge transfer states

Abstract: In this paper the potential energy curves of CT states and their interaction with local ones have been investigated. Besides the global view of these curves, special attention has been paid to the region of the crossing and the infinite separation limit. It was found that triple excitations are needed to accurately describe potential energy surfaces of CT states. Among the cheaper variants, both STEOM-CCSD and CCSD(T)(a)* methods are promising in this respect. The somewhat larger error of CCSD for CT states ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(64 citation statements)
references
References 39 publications
7
47
0
Order By: Relevance
“…∞) still lies below a local excited-state, which is not what it is predicted by CC3 and higher-order methods. 104 The same behavior is expected to be characteristic of other range-separated DH functionals too, further proving that there still is some margin of improvement available for these methods.…”
Section: Potential Energy Curves For Excitation Energiesmentioning
confidence: 76%
See 2 more Smart Citations
“…∞) still lies below a local excited-state, which is not what it is predicted by CC3 and higher-order methods. 104 The same behavior is expected to be characteristic of other range-separated DH functionals too, further proving that there still is some margin of improvement available for these methods.…”
Section: Potential Energy Curves For Excitation Energiesmentioning
confidence: 76%
“…We have chosen the ammonia-fluorine complex, see Figure 3, for which nearly-exact CCSDT-3/cc-pVDZ results are available in both situations (6.62 eV at R = R e and 10.82 eV at R ! ∞, see Table S4) as reference values, 90,104 and checked that the excitation energy at R ! ∞ is always characterized by the CT descriptors Ω POS = 1.5 and Ω CT = 1.0 (see Table S5).…”
Section: Asymptotic Limit Of Inter-molecular Chargetransfer Excitatmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the position of the “crossing” point is an important quantity to reproduce by approximate methods, the single point calculations presented in this work do not allow us to draw a conclusion about the ability of the methods to describe the geometry dependence of the coupling between CT and local states. In a subsequent study 72 we will investigate this problem in detail by comparing the potential energy surfaces obtained by different methods.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigations, based on a set of local and CT states of bimolecular complexes, 31 revealed a significant underestimation of the CT excitation energy at the equilibrium structure of these systems. In ref 32 it was also shown that many issues related to the inappropriate description of CT states are connected to the asymptotic behaviour of the methods, i.e. the description of the charge transfer at infinite separation of the source and destination fragments.…”
Section: Introductionmentioning
confidence: 99%